2020
DOI: 10.1038/s41598-020-66344-8
|View full text |Cite
|
Sign up to set email alerts
|

Using Accelerated Molecular Dynamics Simulation to elucidate the effects of the T198F mutation on the molecular flexibility of the West Nile virus envelope protein

Abstract: The envelope (E) protein is an important target for antibodies in flavivirus. Literature reports that the mutation T198F, located at the domain I-II hinge of the E protein, regulates viral breathing and increases the accessibility of a distal cryptic epitope located on the fusion loop, having a direct impact in the neutralization of West Nile virus (WNV). Our study aimed to describe, using accelerated molecular dynamics simulations, the effects of the T198F mutation in the flexibility of the E protein of WNV a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The principal component analysis (PCA) is a technique that allows to reduce the dimensions of the analyzed trajectories during the MD simulation of the covariance matrix (C), thus reducing the linear correlations between the spatial coordinates and converting them into a set of an orthogonal vector named principal component (PC) which describes the movements using the Cartesian coordinates X , Y , and Z of each analyzed atom 48 . This technique has been widely combined with MD simulations to evaluate the conformational changes of protein structures 40,49‐55 . Here, the CPPTRAJ module available in the Amber16 package was used to obtain the trajectories of Is PETase structures using the Cα coordinates over the 500 ns of MDs to generate the principal components (PC1, PC2, and PC3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal component analysis (PCA) is a technique that allows to reduce the dimensions of the analyzed trajectories during the MD simulation of the covariance matrix (C), thus reducing the linear correlations between the spatial coordinates and converting them into a set of an orthogonal vector named principal component (PC) which describes the movements using the Cartesian coordinates X , Y , and Z of each analyzed atom 48 . This technique has been widely combined with MD simulations to evaluate the conformational changes of protein structures 40,49‐55 . Here, the CPPTRAJ module available in the Amber16 package was used to obtain the trajectories of Is PETase structures using the Cα coordinates over the 500 ns of MDs to generate the principal components (PC1, PC2, and PC3).…”
Section: Methodsmentioning
confidence: 99%
“…48 This technique has been widely combined with MD simulations to evaluate the conformational changes of protein structures. 40,[49][50][51][52][53][54][55] Here, the CPPTRAJ module available in the Amber16 package was used to obtain the trajectories of IsPETase structures using the Cα coordinates over the 500 ns of MDs to generate the principal components (PC1, PC2, and PC3). The principal components that represent the protein movement are described according to Equation (1) [56][57][58] :…”
Section: Principal Component Analysis and Free Energy Landscapementioning
confidence: 99%
“…This work aims to carry out an exhaustive sampling on the different conformations of the protein-protein interface under physiological conditions using accelerated molecular dynamics (aMD), thus analyzing the most favored poses under these conditions by means of its two-dimensional potential of mean force (2D-PMF) considering the binding energy and buried surface interface, to determine the predominant interactions throughout the conformational sampling. Conformational sampling can be achieved using cMD and aMD as it is shown in the bibliography [ 32 , 33 ]. However aMD simulations present a greater efficiency when compared to MD simulation as it was shown by Pierce et al.…”
Section: Introductionmentioning
confidence: 99%
“…It correlates with the protein-solvent hydrogen bond plot, which, although fluctuating, does not exhibit a sudden and sustained spike of protein-solvent hydrogen bonds, as donor and acceptor atoms that had previously established intramolecular hydrogen bonds are exposed and form hydrogen bonds with the water [57][58][59]. The DCCM illustrates movements between individual residues that are considerably correlated in yellow and highly anticorrelated motions in blue [60][61][62] (Figure 8). It is shown that the E5-rimantadine complex enhanced both correlated and anticorrelated motion, implying higher fluctuation and interaction between residues within the complex.…”
Section: Resultsmentioning
confidence: 76%